Piperacillin/tazobactam resistance in a clinical isolate of Escherichia coli due to IS26-mediated amplification of blaTEM-1B. - Hubbard, ATM; Mason, J; Roberts, P; Parry, CM; Corless, C; van Aartsen, J; Howard, A; Bulgasim, I; Fraser, AJ; Adams, ER; Roberts, AP; Edwards, T (Springer Nature, 2020)
A phenotype of Escherichia coli and Klebsiella pneumoniae, resistant to piperacillin/tazobactam (TZP) but susceptible to carbapenems and 3rd generation cephalosporins, has emerged. The resistance mechanism associated with this phenotype has been identified as hyperproduction of the β-lactamase TEM. However, the mechanism of hyperproduction due to gene amplification is not well understood. Here, we report a mechanism of gene amplification due to a translocatable unit (TU) excising from an IS26-flanked pseudo-compound transposon, PTn6762, which harbours blaTEM-1B. The TU re-inserts into the chromosome adjacent to IS26 and forms a tandem array of TUs, which increases the copy number of blaTEM-1B, leading to TEM-1B hyperproduction and TZP resistance. Despite a significant increase in blaTEM-1B copy number, the TZP-resistant isolate does not incur a fitness cost compared to the TZP-susceptible ancestor. This mechanism of amplification of blaTEM-1B is an important consideration when using genomic data to predict susceptibility to TZP.